Zonulin and claudin‐5 levels in multisystem inflammatory syndrome and SARS‐CoV‐2 infection in children. (30th May 2022) - Kılıç, Ahmet O; Akın, Fatih; Yazar, Abdullah; Metin Akcan, Özge; Topcu, Cemile; Aydın, Orkun
Abstract : Aim: SARS‐CoV‐2 infection in children is generally asymptomatic or mild; however, it can lead to a life‐threatening clinical condition, multisystem inflammatory syndrome in children (MIS‐C), days or weeks after the infection. Increased intestinal permeability isa possible triggering factor at the onset of the hyperinflammation associated with MIS‐C. Zonulin and claudin‐5 are involved in intestinal permeability. In this study, we aimed to investigate serum zonulin and claudin‐5 levels in SARS‐CoV‐2 infection and MIS‐C disease. Methods: The study group consisted of children diagnosed with MIS‐C or SARS‐CoV‐2 infection who presented to a university hospital paediatric emergency or infectious diseases departments. The control group included well patients seen at the General Pediatrics units for routine follow‐up. Serum zonulin and claudin‐5 levels were measured at the time of diagnosis. Results: Fifteen patients were included in the MIS‐C group, 19 in the SARS‐CoV‐2 infection group and 21 in the control group. The mean zonulin level in the MIS‐C group was significantly higher than in the control group ( P < 0.001). Mean Claudin‐5 levels were P significantly lower in the SARS‐CoV‐2 infection group than in the control group ( P < 0.001). Conclusion: These results indicate that increased intestinal permeability may be involved in the pathogenesis of SARS‐CoV‐2 infection and MIS‐C disease. Larger clinical trials are needed to clarify the role of serum zonulin and claudin‐5 on intestinal permeability in MIS‐C and SARS‐CoV‐2 infection in children.